The Influence of Interpersonal Communication and Sales Marketing on Customer Loyalty: A Quantitative Study at Astra Motor BSD City - Putri, Safhira Amadea; Sidharta, Veranus; Arlena, Wenny Maya (FISIP UPNVJ, 2025)
Maintaining customer loyalty in the increasingly competitive automotive industry is crucial, where product quality is relatively homogeneous, so interpersonal relationship aspects and marketing strategies become significant differentiating factors. This study aims to analyze the influence of interpersonal communication and sales marketing on customer loyalty at the Astra Motor BSD City Dealer. This study uses a quantitative method with an associative approach. The study population is all Astra Motor BSD City Dealer customers, with a sample size of 100 respondents determined using the Slovin formula. The sampling technique was purposive, while data were collected through a questionnaire with a five-point Likert scale. The study results indicate that interpersonal communication positively and significantly affects customer loyalty, with a regression coefficient of 0.645 and a correlation of 0.885. Similarly, sales marketing is proven to have a significant positive effect with a regression coefficient of 0.435 and a correlation of 0.873. The simultaneous test yielded a calculated F value of 254.903 with a significance of 0.000, while the coefficient of determination (R²) value was 0.815, meaning that these two variables explained 81.5% of customer loyalty. Thus, it can be concluded that interpersonal communication and sales marketing are strategic factors that greatly determine the formation of customer loyalty at the Astra Motor BSD City Dealer.